Per-operative recognition of regional lymph nodes, functionally competent, in malignant neoplasms - Badano Repetto, José Luis; Badano Carbajal, José Luis (Cirugía del Uruguay, 1975)
The authors aim to visualize f.unctionally competent lymph nades by means of per-operative lymphadenochromoscopy, In arder to do so they inject vital stains (patent blue V) in the corresponding lymphatic vessels. There is a correlation betwe.en the studied microscopic anatomy and the staining of the lymph nades. This is also consistent with lymphadenography and lymphadenoscintigraphy. The advantage of lymphadenochrcmoscopy over the above mentioned procedures is that it enables the - direct visualization of the Jymph nades during surgery.